ANALISIS PENGARUH PRODUKSI TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAMBI - Zahrotun Nurfadillah; Anisa Putri Febriyanti; M. Nasrullah; M.Rais; Ary Dean Amry (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Economic growth is related to the role of natural resources, because natural resources are an important factor for realizing economic growth whether economic growth is running as expected. Exports cannot be separated from economic growth while economic growth is driven by production. Based on this, this study aims to determine the effect of production on economic growth in Jambi province. This study uses secondary data types with multiple linear regression data analysis techniques. The testing phase is the classic assumption test consisting of data normality test, multicollinearity test, heteroscedasticity test, autocorrelation test and hypothesis test. The test results show that coal production has no effect on economic growth in Jambi Province in this study period. In partial statistical tests, coal production has no effect on economic growth in Jambi Province.